PROSEDUR PENERIMAAN KAS PADA Mr. LAUNDRY DI KABUPATEN ENDE - Roja, Edeltrudis; Djou, Laurentius Dominicus Gadi (Jurnal Riset Ilmu Akuntansi, 2022)
The formulation of the problem in this study is how is the procedure for cash receipts at Mr. Laundry in Ende Regency. The purpose of this study was to determine the procedure for cash receipts at Mr. Laundry in Ende Regency. The type of research used is descriptive qualitative. Based on the results of observations and interviews, as well as the analysis that has been described, as well as explanations in previous chapters, the authors draw the following conclusions: 1. The accounting system for cash receipts for Laundry services at Mr. Laundry is quite good. This can be seen from the existence of customer acceptance procedures starting from registration until the customer receives the goods from the laundry service. 2. The system and procedures for cash receipts for laundry services at Mr. Laundry are in accordance with the existing system. Clear separation of functions between the Receiving function, the cash receipt function carried out by the cashier and storage and recording and reporting functions carried out by the treasurer. 3. Accounting records have ensured that all transactions that occur are properly recorded and supported by supporting documents that have been authorized by the competent authorities. 4. The laundry service cash receipt system still has several weaknesses, namely in the registration section which still needs to improve service to customers from computerization, but it is necessary to make Data Flow Diagrams or Flowcharts in order to make it easier for users of accounting information.